Construction of Mental Health Education Model Based on Computer Multimedia Group Psychological Measurement. (24th September 2021) - Zhang, Haiyan
Abstract : Modern people's concept of health is more comprehensive; in addition to physical health, they focus on mental health even more. Computer multimedia group psychological measurement is introduced, and a mental health education model is constructed in this paper. The model includes three interrelated levels: mechanism level, evaluation level, and target level. It emphasizes the key and core role of mental quality in mental health. It advocates incorporating mental quality into the evaluation and diagnosis system of the overall state of individual mental health, combines the classified qualitative assessment and quantitative assessment, and arranges appropriate prevention and intervention measures according to different types of individuals. Practice has proved that this method is effective.